Clinical Application of Airway Collapsibility Measurements by Abrupt Interruption of Airflow During Forced Expiration - Sakurai, Shigeru; Huang, Jyongsu; Matsuda, Masafumi; Takase, Keiichiro; Toga, Hirohisa; Maekawa, Yutaka; Ohya, Nobuo; Fukunaga, Toshiharu (Nihon Kyōbu Shikkan Gakkai zasshi, 1987)
We previously introduced a new method for estimating the airway compliance from the mouth-pressure curve obtained after abrupt interruption of airflow during forced expiration. Within about 100msec after the interruption of airflow at the mouth, the pressure curve suddenly increases (first step) and is followed by exponential rise (exponential phase) which reaches the alveolar pressure. Under iso-volume conditions, the exponential phase of the curve, which is effort independent, is determined by the pressure-volume characteristics of the downstream segment below the choke point. Using this method, we measured the airway compliance of the downstream segment below the choke point in patients with tracheobronchopathia osteochondroplastica (TBO), tracheobronchomegaly (TBM), and chronic obstructive pulmonary disease (COPD). According to the wave-speed theory, the maximum flow (Vmax) during forced expiration is limited by the cross-sectional area and the airway collapsibility at the choke point. Fiberoptic bronchoscopy, which demonstrates the cross-sectional area and dynamic properties of the trachea during forced expiration, allowed us to validate our method, and evaluate the airway collapsibility. The TBO patient was shown to have a very hard and narrow trachea by bronchoscopy; it hardly collapsed during cough or forced expiration. Her airway compliance was estimated to be zero at 60% forced vital capacity (FVC). This suggests that the downstream segment did not collapse at 60% FVC. The trachea and main bronchi of the TBM patient collapsed very easily during forced expiration. In this patient the airway compliance value was 1.45ml/cm H2O at 40% FVC, larger than that of normal subjects. In patients with COPD (n=3), the compliance values were 2.0-2.5ml/cm H2O at 50% FVC. These values were larger than those of normal subjects (1.00ml/cm H2O at 50% FVC). This implies that the downstream segment of the airway is collapsible in COPD patients. Considering the clinical, radiographic and endoscopic findings of the patients, we conclude that the values obtained by our method for measuring the airway compliance are reasonable. This method also provides the pressure-volume curve of the airway below the choke point. This curve is influenced by two factors: the location of the choke point and the collapsibility of the downstream airway segment. We think, therefore, that this method is very valuable in detecting functional disorders of the airway and lung. Unfortunately, however, the factors cannot be separated.